Anatomical and physiological changes in pelvic diaphragm in patients with chagasic megacolon submitted to Duhamel surgery - Júnior, Hélio Moreira; Moreira, José P.T.; Isaac, Raniere R.; de Almeida, Arminda C.; Moreira, Hélio; Klug, Wilmar A. (Journal of Coloproctology, 2013)
Original contribution understand the reasons why Duhamel surgery results in clinical improvement of constipation in patients with Chagasic colopathy.Background Duhamel surgery is one of the most widespread techniques for the treatment of Chagasic megacolon, with low rates of recurrence of constipation.Objective evaluate the anatomical and physiological changes in the pelvic diaphragm of patients with chagasic colopathy, as well as changes occurring after undergoing Duhamel surgery.Design clinical data and results of cinedefecography, electromanometry and anorectal ultrasound of the anal canal were evaluated in patients with Chagasic colopathy, before and after Duhamel surgery.Location Service of Coloproctology – Departament of Surgery, Faculdade de Medicina da Universidade Federal de Goiás. Patients: patients with positive serology for Chagas Disease, with constipation and radiological megacolon, who presented consecutively to the Chagas outpatient clinic and freely agreed to participate in this study, were prospectively included.Results a total of 20 patients were included, with a mean age of 53.2 years, of which 16 were women. The following parameters were observed in the postoperative period: change in bowel frequency, of, on average, one evacuation every ten days to daily bowel movement; 16 patients used laxatives preoperatively and only one did, intermittently, in postoperative period. Electromanometry showed, postoperatively, a decrease in anal resting pressure (60.88 to 37.2 mmHg p < 0.001) and anal squeeze pressures (244.3 mL to 161.25 p = 0.01), whereas ultrasound showed that 75% of the patients had abnormalities of the internal anal sphincter in the posterior anal canal juxtaposed to the pulled-through colon. Postoperative rectal emptying observed in cinedefecographic tests occurred more quickly and with less effort when compared with the preoperative findings. There was a change in the anorectal angle postoperatively, which became more obtuse, both during rest, straining and during evacuation.Conclusions the anatomical and functional changes in the pelvic diaphragm are significant after Duhamel surgery and together, they result in clinical improvement of patients.
Keywords: Chagas disease; Megacolon/surgery; Intestinal constipation; Anal canal; Surgical procedures of the digestive system; Perioperative care; Evaluation